HUBUNGAN SOSIAL DAN KEAGAMAAN ANTARA PETANI, SANTRI, DAN PRIYAYI - Raha Bistara (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2021)
This article wants to spread the social and religious relations between farmers, santri, and priyayi which are framed in an Islamic-Javanese frame. The relationship between the three is like a unity that cannot be separated when talking about Islam-Javanese. Islam-Javanese is a unifying identity of Javanese people and as an important identity of Javanese people. When they declare themselves as Javanese, Islam cannot be separated because Java and Islam are a unified identity within Javanese people. By using the library research method, this study wants to explore how the social and religious relations between farmers, santri, and priyayi in the frame made by R.NgYasadipura II in his Serat Sana Sunu which is so Mashur. Piwulang needs to be re-examined in the treasures of Nusantara thought which Until now, not many scholars in Indonesia have touched or even explored this wise treasure. This Piwulang is also an important lesson for scholars who until now are getting away from the lives of their people, which they (graduates) should be the best wasilah in bringing back the treasures of thought of the ancestors.